2011
DOI: 10.1016/j.aat.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect on improvement of recovery and pain scores of paravertebral block immediately before breast surgery

Abstract: PVB given before surgery in combination with GA could provide better postoperative analgesia and better QoR than did GA alone in patients undergoing surgery for unilateral breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…One retrospective study of 526 patients showed that use of paravertebral block vs no paravertebral block significantly decreased need for postoperative emetic rescue, opioid use on the day of surgery, and time to discharge [62]. An additional prospective study showed that use of paravertebral block improved the combined “Quality of Recovery” score on POD 1 [39]. Only one retrospective study of 337 patients was unable to show a significant difference in use of morphine on POD0, pain scores, or nausea when comparing patients receiving paravertebral block vs no paravertebral block for breast cancer surgery [60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One retrospective study of 526 patients showed that use of paravertebral block vs no paravertebral block significantly decreased need for postoperative emetic rescue, opioid use on the day of surgery, and time to discharge [62]. An additional prospective study showed that use of paravertebral block improved the combined “Quality of Recovery” score on POD 1 [39]. Only one retrospective study of 337 patients was unable to show a significant difference in use of morphine on POD0, pain scores, or nausea when comparing patients receiving paravertebral block vs no paravertebral block for breast cancer surgery [60].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of morphine may also contribute to angiogenesis; at medically relevant concentrations, morphine can stimulate not only endothelial proliferation, survival, and cell cycle progression but also angiogenesis in both in vitro and in vivo breast cancer models [38]. It was demonstrated that tramadol, but not morphine can overcome the ability of surgical stress to decrease the activity of NK cells in rats perhaps accounting for tramadol’s ability to block lung metastasis in rats [39, 40]. Further supporting the presumed immunosuppressive role of morphine, one study looking at opioids administered to patients for acute postoperative pain, found that morphine caused a decrease in lymphocyte proliferation below basal levels 2 hours after treatment whereas tramadol-treated patients’ lymphocyte counts returned to baseline in the same time period [41].…”
Section: Opioidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 22-gauge, 3.5-in spinal needle (Terumo ® spinal needle, Terumo Corporation, Tokyo, Japan) was subsequently inserted according to a previously described method [13]. Moreover, 8 mL of 0.5% levobupivacaine with 1:400,000 epinephrine was injected after negative aspiration of blood, air, or cerebrospinal fluid at the T2, T4, and T6 levels.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered that, acute postoperative pain after breast surgery is around 40%, and this rate becomes much higher as result of inadequate pain management. 40 TPVB application after mastectomy improves shoulder movement restricted due to pain. 41 Karmakar 40 a has been reported that the duration of postoperative analgesia was average of 23 hours (range 9-38 hours) fort he patients applied TPVB by bolus injection.…”
Section: Anesthesia For Breast Surgerymentioning
confidence: 97%